Preparation method for reducing silicon carbide crystal defects
By filling the conductive silicon carbide layer and ceramic layer on the silicon carbide raw material, the defect problem caused by imbalance of impurities and silicon components in the growth of silicon carbide single crystals is solved, and the growth and cost reduction of high-quality silicon carbide crystals are achieved.
Patent Information
- Application Number
- CN202411992922.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
During the growth of silicon carbide single crystals, imbalance of impurities and silicon components leads to defects in the crystals such as microtubules, wraps and dislocations.
A preparation method is adopted, including filling a conductive silicon carbide layer and a ceramic layer above the silicon carbide raw material, the ceramic layer serves as a buffer layer for the gas phase components, and the conductive silicon carbide layer to increase the concentration of the gas phase components.
The encasement defects and total dislocations in the silicon carbide crystal are significantly reduced, the quality and yield of the crystal are improved, and the production cost is reduced.
Smart Images

Figure CN119776979A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon carbide processing, and in particular to a preparation method for reducing silicon carbide crystal defects. Background Art
[0002] In the process of growing silicon carbide single crystals by physical vapor transport, on the one hand, various impurities are inevitably present in the silicon carbide raw materials. These impurities will also sublimate into the gas phase with the raw materials at high temperatures, and gather to form impurity particles on the growth surface of the seed crystal and in the crystal, further causing defects such as microtubes, inclusions and dislocations; on the other hand, due to the low melting point of the silicon component, it will evaporate and sublimate preferentially, and penetrate outward through the wall of the graphite crucible. As the reaction proceeds, the Si / C ratio gradually decreases, causing the gas phase components in the growth chamber to gradually become unbalanced and become carbon-rich. In a carbon-rich growth environment, carbon will be enriched at the interface of the crystal growth front and form carbon inclusion defects. Inclusions will then induce defects such as microtubes, dislocations, and stacking faults. Summary of the invention
[0003] In order to solve the technical problems existing in the above background technology, the object of the present invention is to provide a preparation method for reducing silicon carbide crystal defects, comprising the following steps:
[0004] S0, loading silicon carbide raw material into a crucible;
[0005] S1, filling a conductive silicon carbide layer on the silicon carbide raw material, the purity of the conductive silicon carbide is more than 99%;
[0006] S2, filling a ceramic layer on top of the conductive silicon carbide layer;
[0007] S3, connecting the silicon carbide seed crystal to the crucible cover, and placing the crucible into the silicon carbide crystal growth furnace.
[0008] The preferred technical solution of the present invention is that the thickness of the ceramic layer is 0.5-5 mm, and the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 20-50 mm.
[0009] A preferred technical solution of the present invention is that the ceramic layer is composed of one or more of tantalum carbide, tungsten carbide, molybdenum carbide, osmium carbide, iridium carbide, rhenium carbide, niobium carbide, titanium carbide, zirconium carbide, and yttrium carbide.
[0010] The preferred technical solution of the present invention is that the surface area of the ceramic layer is equal to the surface area of the silicon carbide raw material. The surface area referred to in the technical solution refers to the area of a horizontal circle, and the ceramic layer directly covers the silicon carbide raw material, and the areas of the two are consistent.
[0011] A preferred technical solution of the present invention is that the ceramic layer is ceramic particles, and the size of the ceramic particles is 10 μm-10 mm.
[0012] A preferred technical solution of the present invention is that the porosity of the ceramic layer is 25%-75%.
[0013] A preferred technical solution of the present invention is that the conductive silicon carbide layer is prepared by chemical vapor deposition.
[0014] A preferred technical solution of the present invention is that the conductive silicon carbide layer is powder particles with a particle size of 400 μm to 700 μm.
[0015] A preferred technical solution of the present invention is that the porosity of the conductive silicon carbide layer is 20%-35%.
[0016] A preferred technical solution of the present invention is that the purity of the conductive silicon carbide layer is above 99.9999%.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The ceramic layer is resistant to high temperatures and has stable chemical properties. It will not cause metal contamination to the crystal and can be reused. In addition, the ceramic layer can be used as a buffer layer for the gas phase components when the silicon carbide raw material sublimates, allowing a more stable raw material gas flow in the crucible chamber and stabilizing the growth rate;
[0019] 2. The high-purity conductive silicon carbide powder has high purity, and the silicon-carbon ratio is closer to 1:1 during sublimation, which reduces the probability of defects in silicon carbide crystals. In addition, the high-purity conductive silicon carbide powder is easier to sublimate, plays a guiding role, and increases the concentration of gas phase components in the crucible, thereby further accelerating the sublimation of silicon carbide raw materials, improving the growth efficiency of crystals, and reducing growth time.
[0020] 3. The ceramic layer and high-purity conductive silicon carbide powder work together to significantly reduce the inclusion defects in the crystal, reduce the total dislocation, obtain high-quality silicon carbide crystals, and improve the yield of silicon carbide crystal growth. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 Schematic diagram of the raw material distribution structure inside the crucible in an embodiment of the present invention.
[0023] In the figure:
[0024] 1-crucible; 11-crucible cover; 2-silicon carbide raw material; 3-conductive silicon carbide layer; 4-ceramic layer; 5-silicon carbide seed crystal; 6-graphite paper. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0026] The following Table 1 lists the sources and types of raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the reagents were all commercially available.
[0027] Table 1 - Sources and models of raw materials in the examples of this application
[0028]
[0029] The raw material distribution structure inside the crucible of the following embodiments is as follows: Figure 1 As shown, the bottom of the crucible 1 is a flattened silicon carbide raw material 2, a flattened conductive silicon carbide layer 3 is arranged above the silicon carbide raw material 2, a flattened ceramic layer 4 is arranged above the conductive silicon carbide layer 3, the ceramic layer 4 is 3 mm thick, and above the ceramic layer 4 is a crucible cover 11, the crucible cover 11 is connected to the silicon carbide seed crystal 5, and an insulating graphite paper 6 is arranged between the crucible cover 11 and the silicon carbide seed crystal 5.
[0030] Examples 1-6 and Comparative Examples 1-2
[0031] Example 1
[0032] A preparation method for reducing silicon carbide crystal defects comprises the following steps:
[0033] Step 1, put 2000g of silicon carbide raw material into a crucible;
[0034] Step 2, a conductive silicon carbide layer is loaded on the silicon carbide raw material, and the high-purity silicon carbide powder-1 used is 250g;
[0035] Step 3, a ceramic layer is loaded on the conductive silicon carbide layer, and the ceramic particles-1 used are 2000g;
[0036] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0037] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere;
[0038] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0039] Example 2
[0040] A preparation method for reducing silicon carbide crystal defects comprises the following steps, wherein the amount of raw materials used is the same as that of Example 1:
[0041] Step 1, loading silicon carbide raw material into a crucible;
[0042] Step 2, filling a conductive silicon carbide layer on top of the silicon carbide raw material, using high-purity silicon carbide powder-2;
[0043] Step 3, filling a ceramic layer on the conductive silicon carbide layer, using ceramic particles-1;
[0044] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0045] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere.
[0046] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0047] Example 3
[0048] A preparation method for reducing silicon carbide crystal defects comprises the following steps, wherein the amount of raw materials used is the same as that of Example 1:
[0049] Step 1, loading silicon carbide raw material into a crucible;
[0050] Step 2, filling a conductive silicon carbide layer on top of the silicon carbide raw material, using high-purity silicon carbide powder-1;
[0051] Step 3, filling a ceramic layer on the conductive silicon carbide layer, using ceramic particles-2;
[0052] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0053] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere;
[0054] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0055] Example 4
[0056] A preparation method for reducing silicon carbide crystal defects comprises the following steps, wherein the amount of raw materials used is the same as that of Example 1:
[0057] Step 1, loading silicon carbide raw material into a crucible;
[0058] Step 2, filling a conductive silicon carbide layer on top of the silicon carbide raw material, using high-purity silicon carbide powder-1;
[0059] Step 3, filling a ceramic layer on the conductive silicon carbide layer, using ceramic particles-3;
[0060] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0061] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere;
[0062] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0063] Example 5
[0064] A preparation method for reducing silicon carbide crystal defects comprises the following steps, wherein the amount of raw materials used is the same as that of Example 1:
[0065] Step 1, loading silicon carbide raw material into a crucible;
[0066] Step 2, filling a conductive silicon carbide layer on top of the silicon carbide raw material, using high-purity silicon carbide powder-1;
[0067] Step 3, a ceramic layer is filled on the conductive silicon carbide layer, and a mixture of ceramic particles-1, ceramic particles-2, and ceramic particles-3 is used. The three are fully stirred and evenly mixed before use, and the weight ratio thereof is 1:1:1;
[0068] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0069] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere;
[0070] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0071] Example 6
[0072] A preparation method for reducing silicon carbide crystal defects comprises the following steps:
[0073] Step 1, put 2000g of silicon carbide raw material into a crucible;
[0074] Step 2, a conductive silicon carbide layer is loaded on the silicon carbide raw material, and the high-purity silicon carbide powder-1 used is 150g;
[0075] Step 3, a ceramic layer is loaded on the conductive silicon carbide layer, and the ceramic particles-1 used are 2000g;
[0076] Step 4, connect the silicon carbide seed crystal to the crucible cover, the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 50 mm, and put the crucible into the silicon carbide crystal growth furnace;
[0077] Step 5, growth power 11 kW, temperature 2300°C, pressure 300 Pa, argon atmosphere;
[0078] After the crystal is grown to a thickness of 16 mm, a silicon carbide crystal is obtained, and the corresponding growth time is recorded.
[0079] Comparative Example 1
[0080] A method for preparing silicon carbide crystals, which differs from Example 1 in that the step of filling a conductive silicon carbide layer in step 2 is missing.
[0081] Comparative Example 2
[0082] A method for preparing silicon carbide crystals, which differs from Example 1 in that the conductive silicon carbide layer and the ceramic layer loaded in steps 2 and 3 are missing.
[0083] The silicon carbide crystals obtained in the above examples and comparative examples were subjected to the following tests.
[0084] Testing methods;
[0085] Defect test method of silicon carbide crystal: take the front and back slices of the crystal for testing, observe the inclusions of the slices, and use potassium hydroxide corrosion method to detect total dislocations. The test results are shown in Table 2;
[0086] Surface test method of silicon carbide crystal: Defects were observed through 8520 microscope, and the test results are shown in Table 2;
[0087] Growth rate stability of silicon carbide crystal: The resistance trend of the crystal after slicing is tested to determine whether the growth rate is stable. If the curve shows a steady or slow change, the growth rate is stable. If the curve shows obvious fluctuations or mutations, it indicates that the growth rate of the crystal is unstable. The test results are shown in Table 2.
[0088] The results of the above test method are shown in Table 2.
[0089] Table 2 - Performance test results of examples and comparative examples
[0090]
[0091] As can be seen from the table above, the growth time of the silicon carbide crystal prepared in the embodiment of the present invention is 85-92h, the growth is stable, and the crystal defect is good, there is no inclusion, the total dislocation is low, and the number is 1000-3000 / cm 2 , compared with 8741 pieces / cm in Comparative Example 1 2 And 12486 pieces / cm in Comparative Example 2 2 , with obvious improvement, and the crystal surface prepared in the embodiment is smooth, free of impurity particles, and is a high-quality silicon carbide crystal. Importantly, the preparation method of the present invention can select silicon carbide raw materials with lower purity to prepare high-quality silicon carbide crystals, without the need to use silicon carbide raw materials with a purity of more than 99% in the traditional process, thereby reducing production costs and improving the utilization rate of low-quality raw materials.
[0092] By comparing Example 1 and Example 2, it can be seen that the high-purity silicon carbide powder prepared by chemical vapor deposition has a more uniform particle size, a faster evaporation efficiency during subsequent crystal growth, and a lower total dislocation of the grown crystal, and the quality of the obtained silicon carbide crystal is higher.
[0093] By comparing Example 1 and Example 5, it can be seen that when the ceramic particles used are a composite of three types (tungsten compound, molybdenum compound, tantalum compound), and the ratio of the three is the same, the prepared silicon carbide crystal has a shorter growth time and more stable quality. The inventors believe that when tungsten, molybdenum, and tantalum compounds are composited, they may produce a synergistic catalytic effect, which may further accelerate the growth rate of silicon carbide crystals and improve the quality of the crystals. For example, they may change the gas composition, temperature distribution, or pressure conditions in the crucible, thereby facilitating the rapid and stable growth of crystals.
[0094] From the comparison between Example 1 and Example 6, it can be seen that when the amount of high-purity silicon carbide powder used is reduced, the growth time of the prepared silicon carbide crystal will be slightly increased, and the total dislocations will also increase to 2418 / cm 2 According to the inventor's research and experiments, it is more appropriate when the ratio of silicon carbide raw material to high-purity silicon carbide powder is less than 10:1.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for reducing silicon carbide crystal defects, characterized in that: The following steps are involved: S0, loading silicon carbide raw material into a crucible; S1, filling a conductive silicon carbide layer on the silicon carbide raw material, wherein the purity of the conductive silicon carbide is more than 99%; S2, filling a ceramic layer on top of the conductive silicon carbide layer; S3, connecting the silicon carbide seed crystal to the crucible cover, and placing the crucible into the silicon carbide crystal growth furnace.
2. The preparation method according to claim 1, characterized in that: The thickness of the ceramic layer is 0.5-5 mm, and the vertical distance between the ceramic layer and the lower surface of the silicon carbide seed crystal is 20-50 mm.
3. The preparation method according to claim 1, characterized in that: The ceramic layer is composed of one or more of tantalum carbide, tungsten carbide, molybdenum carbide, osmium carbide, iridium carbide, rhenium carbide, niobium carbide, titanium carbide, zirconium carbide and yttrium carbide.
4. The preparation method according to claim 1, characterized in that: The surface area of the ceramic layer is equivalent to the surface area of the silicon carbide raw material.
5. The preparation method according to claim 1, characterized in that: The ceramic layer is ceramic particles, and the size of the ceramic particles is 10 μm-10 mm.
6. The preparation method according to claim 1, characterized in that: The porosity of the ceramic layer is 25%-75%.
7. The preparation method according to claim 1, characterized in that: The conductive silicon carbide layer is prepared by chemical vapor deposition.
8. The preparation method according to claim 1, characterized in that: The conductive silicon carbide layer is powder particles, and the particle size thereof is 400 μm to 700 μm.
9. The preparation method according to claim 1, characterized in that: The porosity of the conductive silicon carbide layer is 20%-35%.
10. The preparation method according to claim 1, characterized in that: The purity of the conductive silicon carbide layer is above 99.9999%.